Teaching the Arabic Language by the Mean of Soft and Aural-Oral Approach - Adam Doni Mauladi; Muhammad Humamvidi Hunafa; Rizqy Maulana Hakim; Yudo Rahmadiansyah Putra (Proceeding of International Conference on Islamic Education, 2018)
In today’s Indonesia, the Arabic language is not very popular among the population. Even though Indonesia is the most populous Muslim country in the world, Muslims in Indonesia tend to have this “neglection” feeling on the importance of learning the Arabic language. This feeling is caused by the rise of bad sentiment towards Islam and Arab in the world particularly in the west which also influenced Indonesians mindset. The dichotomy which stated the Arabic language as a backward language and the terrorist language further escalate this unpopularity which creates the discouragement of the citizen to learn Arabic by the popular opinion. The problem which has been stated could be solved by further examining Islamic education curriculum especially the Arabic language to be more relevant with the modern world. Seeing the fact that the Arabic language is not a popular subject to be learned, then teaching it should further be with the way that is familiar to the student and easy-going. The Arabic language should be taught with soft and aural-oral approach. Soft approach means that it should be taught casually, while aural-oral approach means that the Arabic language should firstly be taught with conversation style teaching that emphasizes in speaking and understanding of the word and its roots. This study shall examine the problem stated above and the reason why soft and aural-oral approach should be used. it is hoped that by examining this approach, the soft and aural-oral approach could be implemented in the Arabic language classes in Indonesia.